Paraneoplastic itch: an expert position statement from the Special Interest Group (SIG) of the International Forum on the Study of Itch (IFSI) - Weisshaar, Elke; Weiß, Melanie; Mettang, Thomas; Yosipovitch, Gil; Zylicz, Zbigniew (Acta dermato-venereologica, 2015)
In clinical practice, the term "paraneoplastic itch" is used to describe itch in patients with cancer. Patients with hematological or solid tumor malignancies can be affected. In general, paraneoplastic itch is considered a rare disorder. However, paraneoplastic itch in hematological malignancies such as polycythemia vera and lymphoma are relatively frequent while other forms of paraneoplastic itch are in fact extremely rare. The true frequency of this symptom is unclear, epidemiological data in this field are limited. Itch in malignant disease may additionally impair patients' quality of life. A population-based cohort study showed that chronic itch without concomitant skin changes is a risk factor for having undiagnosed hematologic and bile duct malignancies. Paraneoplastic itch is rather resistant to treatment. In 2012, an interdisciplinary interest group of physicians and researchers was founded, aiming to generate a clear definition of paraneoplastic itch. In this paper we briefly review the current knowledge and aim to define what can be summarized under the term "paraneoplastic itch".